Impact of Guidelines Regarding Dihydropyrimidine Dehydrogenase (DPD) Deficiency Screening Using Uracil-Based Phenotyping on the Reduction of Severe Side Effect of 5-Fluorouracil-Based Chemotherapy: A Propension Score Analysis - Nicolas Laures; Céline Konecki; Mathias Brugel; Anne-Lise Giffard; Naceur Abdelli; Damien Botsen; Claire Carlier; Claire Gozalo; Catherine Feliu; Florian Slimano; Zoubir Djerada; Olivier Bouché (MDPI AG, 2022)
Dihydropyrimidine dehydrogenase (DPD) deficiency is associated with severe fluoropyrimidines-induced toxicity. As of September 2018, French recommendations call for screening for DPD deficiency by plasma uracil quantification prior to all fluoropyrimidine-based chemotherapy. A dose reduction of fluoropyrimidine is recommended when uracil concentration is equal to or greater than 16 ng/mL. This matched retrospective study assessed the impact of DPD screening on the reduction of severe side effects and on the management of DPD-deficient patients. Using a propensity score, we balanced the factors influencing 5-Fluorouracil (5-FU) toxicity. Then, the severity scores (G3 and G4 severity as well as their frequency) of patients who did not benefit from DPD screening were compared with those of patients who benefited from DPD screening for each treatment cycle (from 1 to 4). Among 349 screened patients, 198 treated patients were included. Among them, 31 (15.7%) had DPD deficiency (median uracilemia 19.8 ng/mL (range: 16.1-172.3)). The median toxicity severity score was higher in the unscreened group for each treatment cycle (0 vs. 1, p < 0.001 at each cycle from 1 to 4) as well as the cumulative score during all courses of treatment (p = 0.028). DPD-deficient patients received a significantly lower dose of 5-FU (p < 0.001). This study suggests that pretherapeutic plasmatic uracil assessment, along with 5-FU dosage adjustment, may be beneficial in reducing 5-FU toxicity in real-life patients.